Building Interpersonal Communication Through The Local History Dramatic Role Play - Muhammad Syukri; Somadi Sosrohadi; Fatimah Hidayahni Amin (Hasanuddin University, 2023)
Today, in higher education, at the university level, the learning process is still evolving. The objective of this study was describe how to use local role-playing activities for interpersonal communication among students, especially those who have completed semester 5, in order to improve their language skills. In this way, knowledge can explicitly test the order of the function studied and explored by students to help them understand the concept of learning. The study design uses a quantitative survey as the approach, while observation and questionnaire are for data collection. The results show that the local history role-playing method is effective in building interpersonal communication, especially for the 5th-grade English curriculum. A local drama using the “Topekkong Agreement” was indicated where students always express their ideas which the listener can understand and then give feedback or response. So, this method could improve students' English skills. This study recommends that further research is needed to develop methods, especially building interpersonal communication by using a local history drama approach.